2012
DOI: 10.1371/journal.pone.0037154
|View full text |Cite
|
Sign up to set email alerts
|

Failure of A Novel, Rapid Antigen and Antibody Combination Test to Detect Antigen-Positive HIV Infection in African Adults with Early HIV Infection

Abstract: BackgroundAcute HIV infection (prior to antibody seroconversion) represents a high-risk window for HIV transmission. Development of a test to detect acute infection at the point-of-care is urgent.MethodsVolunteers enrolled in a prospective study of HIV incidence in four African cities, Kigali in Rwanda and Ndola, Kitwe and Lusaka in Zambia, were tested regularly for HIV by rapid antibody test and p24 antigen ELISA. Five subgroups of samples were also tested by the Determine Ag/Ab Combo test 1) Antigen positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 16 publications
2
22
0
Order By: Relevance
“…The DHC package insert reports 25 pg/ml as the lower limit of p24 antigen detection and independent studies confirmed the lower limit to be 20–50 pg/ml when using serial dilutions of p24 antigen serum control [37], [42]. However, the p24 antigen lower limit of detection for clinical specimens appears higher: in one study 51 antigen positive plasma specimens ranging 8–457 (median 94) pg/ml remained undetected [42]; and in our study nine fingerstick blood specimens ranging 66–701 (median 115) pg/ml remained undetected. Hence, the DHC antigen lower limit of detection when used with clinical specimens, as opposed to serum control specimens, requires further investigation and clarification.…”
Section: Discussionmentioning
confidence: 97%
“…The DHC package insert reports 25 pg/ml as the lower limit of p24 antigen detection and independent studies confirmed the lower limit to be 20–50 pg/ml when using serial dilutions of p24 antigen serum control [37], [42]. However, the p24 antigen lower limit of detection for clinical specimens appears higher: in one study 51 antigen positive plasma specimens ranging 8–457 (median 94) pg/ml remained undetected [42]; and in our study nine fingerstick blood specimens ranging 66–701 (median 115) pg/ml remained undetected. Hence, the DHC antigen lower limit of detection when used with clinical specimens, as opposed to serum control specimens, requires further investigation and clarification.…”
Section: Discussionmentioning
confidence: 97%
“…Reported sensitivities varied from 0% (0/2 samples;3 0/8,4), 0% (0/13,5), 3% (1/34,6), 23% (13/57,7), 50% (3/6,8), 54% (14/269) to 67% (26/3910). …”
Section: Introductionmentioning
confidence: 99%
“…The Determine HIV-1/2 Ag/Ab combo rapid test is the first such test that detects both Ag and Ab in two separate indicator lines. Early data on the performance of the Determine combo test to detect acute HIV infections in seroconversion panels suggested that it had a good performance in detecting early infections (19,20 (21)(22)(23)(24)(25)(26)(27)(28). Several of the studies were limited by small sample size and failure to follow up potential acute infections for seroconversion.…”
mentioning
confidence: 99%